Pranic (Energy) Healing as a Traditional Therapy: A Quasi-Experimental Study on Pain Management - Surve, Kazanfar; Sayyed, Zakiya; Reji, Sithu; Bawanthade, Karan (Journal of Neonatal Surgery, 2025)
This study investigates the effectiveness of energy healing therapy in reducing pain among adults suffering from physical, emotional, and mental health issues. A quasi-experimental design was employed, with pre- and post-therapy assessments conducted on 51 participants at a Pranic Healing centre in Pune, India. Pain levels were measured on a scale of 1 to 10 before and after therapy sessions. Statistical analysis revealed a moderate negative correlation (r = −0.612, p < 0.05) between the number of sessions and pain reduction, indicating that fewer sessions were associated with greater pain reduction. The regression model explained 37% of the variance in pain reduction (R² = 0.37). These findings suggest that energy healing therapy effectively reduces pain, particularly in the initial sessions. The study highlights the potential of energy healing as a complementary therapy for pain management and calls for further research with controlled designs